Retinal blood flow is increased in type 1 diabetes mellitus patients with advanced stages of retinopathy. Issue 1 (December 2016) - Nguyen, Hoang-Ton; van Duinkerken, Eelco; Verbraak, Frank; Polak, Bettine; Ringens, Peter; Diamant, Michaela; Moll, Annette
Abstract Background Diabetic retinopathy (DRP) is a common microvascular complication seen in patients with type 1 diabetes mellitus (T1DM). The effects of T1DM and concomitant (proliferative) DRP on retinal blood flow are currently unclear. Therefore, we measured retinal vascular blood flow in T1DM patients with and without DRP and non-diabetic controls. We further assessed the acute effects of panretinal photocoagulation on retinal microvascular bloodflow in eight patients with diabetes. Methods Thirty-three T1DM patients with proliferative DRP, previously treated with panretinal photocoagulation (pDRP), 11 T1DM patients with untreated non-proliferative retinopathy (npDRP) and 32 T1DM patients without DRP (nDRP) were compared with 44 non-diabetic gender-matched controls. Using scanning laser Doppler flowmetry (HRF, Heidelberg) blood flow in the retinal microvasculature was measured temporal and nasal of the optic disc and averaged into one flow value per eye. The right eye was used as a default for further analyses. Eight patients with novel proliferative retinopathy (4 T1DM and 4 with type 2 diabetes) were measured before and several months after photocoagulation. Between-group differences in retinal blood flow were assessed using ANOVA corrected for multiple comparisons (Bonferroni). Results Retinal blood flow was higher in the treated pDRP compared with the nDRP group and controls (allP Bonferroni < 0.01). Furthermore, there was a positive linear trend for blood flow with lowest blood flow in the control group and highest in the pDRP group (P -for-trend < 0.01). In the eight patients with novel proliferative retinopathy, blood flow did not significantly change before and after panretinal photocoagulation (P > 0.05). Using regression analysis, no variables were found as predictors of retinal blood flow. Conclusions In comparison with controls and nDRP patients, retinal blood flow significantly increased in the pDRP group, which previously underwent photocoagulation treatment, but not in the npDRP patients. These changes may be a consequence of a failing vascular autoregulation in advanced diabetic retinopathy.